Exploring the Perspectives and Parental Roles in the Academic Performance of University Students with Disabilities - Mntambo, Sithabile Joy; Hlengwa, Wellington Mthokozisi; Adam, Jamila Khatoon; Krishna, Suresh Babu Naidu (African Journal of Inter/Multidisciplinary Studies, 2025)
The present study focusses on exploring the impact of parental support on the academic performance of students with disabilities. A qualitative study approach was used to explore students with disabilities' perspectives of parental support and the impact it has on their academic performance. This qualitative study purposively selected eight participants. They were subjected to semi-structured, open-ended, one-on-one interviews, and these interviews were recorded using an audio recorder with their permission. The collected data was analysed using thematic content analysis. Parental support may take numerous forms, including emotional, physical, and financial assistance. As a result, parental support influences academic success and the adjustment of students living with disabilities to their new environment. However, parental knowledge, attitudes, and tolerance of a student's disability have been shown to be obstacles to meaningful parental support. This study concludes that for students with disabilities to perform to their maximum potential, parents must be trained and empowered to provide necessary support including motivating their children.